Saving Children, Damning Adults? An Examination of Public Support for Juvenile Rehabilitation and Adult Punishment. (December 2019) - Welch, Kelly; Butler, Leah Fikre; Gertz, Marc
Research shows that public preferences about justice system approaches to decreasing illegal behavior distinguish between adult and juvenile offending. We also know that fear of crime and perceived risk of victimization typically strengthen support for harsh punishments and reduce support for rehabilitation. What has yet to be demonstrated—and that we examine here—is whether there are youth-specific differences in the way that crime salience affects public support for punitive versus rehabilitative policies and to what extent confidence in the criminal and juvenile justice systems affects punishment orientations toward adults and juveniles. Essentially, we examine why some Americans support "child saving" yet condemn adults. This exploratory study's findings indicate that while crime salience increases the likelihood that one will support harsh adult criminal measures, it is not associated with similar attitudes toward juvenile delinquents. Further, those for whom crime salience is lower have a greater probability of supporting rehabilitation for both juveniles and adults. Finally, results show that support for the rehabilitation of youth persists despite crime salience among those who are otherwise punitive toward adults. Justice ideology appears unaffected by confidence in the justice systems. Policy implications and recommendations for future research are offered.